Pengaruh Pelatihan Dalam Meningkatkan Kinerja Individu Di Pt Chang Shin Indonesia - Rima Dwi Puspita; Solehudin Solehudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
Training has an important role in improving individual performance in the work environment. PT Chang Shin Indonesia, as a company concerned with employee development, understands the importance of investing in training to improve the quality and effectiveness of its workforce. This article aims to explain the effect of training on individual performance at PT Chang Shin Indonesia. This study uses the interview method using a sample of 10 employees who work at PT Chang Shin Indonesia. The results of the research that has been done is that training has a positive and significant impact on employee work productivity, it can be that training has a positive influence in improving individual performance at PT Chang Shin Indonesia. It can be concluded that through training in skills, knowledge, motivation, productivity, and employee retention, training provides significant benefits for companies. Therefore, PT Chang Shin Indonesia must continue to invest in an effective training program to ensure employees have the necessary resources to be successful in their jobs.